Կաթնաթթվային նոր պրոբիոտիկային շտամների հիման վրա ստացված յոգուրտների կենսաանվտանգության մի շարք ցուցանիշներ - Բատիկյան,Հ. Գ.; Միրզաբեկյան, Ս. Ս.; Հարությունյան, Ն. Ա.; Փեփոյան, Ա. Զ. (ՀԱԱՀ հիմնադրամ)
Կաթնաթթվային պրոբիոտիկները և դրանց հիման վրա ստացված յոգուրտները անվնաս են առողջության համար, թեև, ըստ որոշ ուսումնասիրությունների, այս պրոբիոտիկները ևս, օրինակ, կարող են համապատասխան հակաբիոտիկների նկատմամբ դրսևորել դիմադրողականություն, ինչը հակաբիոտիկակայունության գեների տարածման տեսանկյունից վտանգավոր է։ Ուստի խնդիր է դրվել ուսումնասիրել Lpb. plantarum ZPZ, Lcb. rhamnosus str. Vahe.am, Lpb. plantarum K1-3, L. delbrueckii IAHAHI պրոբիոտիկային շտամների հիման վրա ստացված յոգուրտների կենսաանվտանգության մի շարք ցուցանիշներ։ Молочнокислые пробиотики и полученные на их основе йогурты безвредны для здоровья, хотя, по данным некоторых исследований, эти пробиотики также могут проявлять устойчивость к соответствующим антибиотикам, что опасно с точки зрения распространения генов антибиотикорезистентности. Поэтому была поставлена задача изучить ряд показателей биобезопасности йогуртов, полученных на основе пробиотических штаммов Lpb. plantarum ZPZ, Lcb. rhamnosus str. Vahe.am, Lpb. plantarum K1-3, L. delbrueckii IAHAHI. Согласно результатам исследований, предлагаемые йогурты соответствуют международным стандартам. In recent years, the use of probiotics has increased unprecedently, regardless of their origin and characteristics. In particular, the use of probiotics for nutritional and therapeutic purposes in infants and patients with a number of diseases (malignant neoplasms, diabetes, post-transplant period, etc.) needs reviews and clinical justification. Currently, in the production of dairy products, lactic acid bacteria (LAB) of intestinal origin are of particular interest, which is explained by the fact that the final target of probiotics is the intestine of an animal or a person. However, there is some skepticism about the efficacy of using human gut-derived LABs in dairy production. LABs are widespread in nature: exist in large quantities in plant residues, soil, human and animal intestines. LABs are widely used both in health care and agriculture, as well as in fisheries and fish production. A task was set up to study a series of biosafety indicators of yoghurts obtained from the Lpb. plantarum ZPZ, Lcb. rhamnosus str. Vahe.am, Lpb. plantarum K1-3, L. delbrueckii IAHAHI probiotic strains. Yoghurts produced with biosafety indicators corresponding to the risk of spreading antibiotic resistance in yoghurts, heavy metals and M1 aflatoxin content, as well as to international standards for microbiological indicators were obtained from new probiotics isolated from the intestinal microbiota of children (Lpb. plantarum ZPZ, Lcb. rhamnosus str. Vahe) and dairy products (Lpb. plantarum K1-3, L. delbrueckii IAHAHI). The results of our research prove that yoghurts obtained from lactic acid bacteria of different origins are harmless to health.
Keywords: Սննդագիտություն և տեխնոլոգիա